# 27c+38cdg=

## Simple and best practice solution for 27c+38cdg= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 27c+38cdg= equation:

Simplifying
27c + 38cdg = 0

Solving
27c + 38cdg = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'c'.
c(27 + 38dg) = 0

Subproblem 1Set the factor 'c' equal to zero and attempt to solve:

Simplifying
c = 0

Solving
c = 0

Move all terms containing c to the left, all other terms to the right.

Simplifying
c = 0
Subproblem 2Set the factor '(27 + 38dg)' equal to zero and attempt to solve:

Simplifying
27 + 38dg = 0

Solving
27 + 38dg = 0

Move all terms containing c to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 38dg = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 38dg = 0 + -27
38dg = 0 + -27

Combine like terms: 0 + -27 = -27
38dg = -27

Add '-38dg' to each side of the equation.
38dg + -38dg = -27 + -38dg

Combine like terms: 38dg + -38dg = 0
0 = -27 + -38dg

Simplifying
0 = -27 + -38dg

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.Solutionc = {0}`